Nilai Kearifan Ekologis dalam Mitos Lelipi Selahan Bukit Bagi Masyarakat Desa Tenganan Pegringsingan Kabupaten Karangasem Bali - Angga Bayu Aditya, I Kadek; Arsana, I Gst Ketut Gde; Suarsana, I Nyoman (Humanis; Vol 22 No 1 (2018), 2018)
The discourse on the environment is now very hot discussed because of the destruction of forest areas in various countries, including Indonesia. In the life of Tenganan Pegringsingan Village community there is a mysterious mystery myth or Lelipi Selahan Bukit who is believed to guard the forest area of ??Tenganan Pegringsingan. The existence of these myths indirectly provide a good impact for the environment around for making forest sustainability in the region Tenganan Pegringsingan become awake. This study raises two issues, the first of which values ??of ecological wisdom contained in the myth of Lelipi Selahan Bukit and the second, how the myth of Lelipi Selahan Bukit in the life of the people of Tenganan pegringsingan Village. This study aims to reveal the myth of Lelipi Selahan Bukit as the ecological wisdom of the local community, in an effort to preserve the forest area. This research uses an ethnoecological approach that depicts the environment as seen by the community under study. This study uses the interpretive theory of Clifford Geertz in expressing local people's thoughts on the myth of Lelipi Selahan Bukit. The research method used is the ethnographic research model that goes into qualitative research by doing observation and interview.The results of this study answer two problems, first reveals the existence of hidden rationality behind the myth of Lelipi Selahan Bukit. The existence of this myth as an ecological wisdom is like a natural fortress that guards the forest area Tenganan Pegringsingan. Second, the emergence of critical thinking from persons who interpret the existence of this myth is not a seed of disunity, this difference of view can enrich the reference of meaning of a phenomenon that occurs in society.